Idiopathic granulomatous hepatitis and abdominal pain. Issue 655 (May 1980) - Shee, C. D.; Creamer, B.
Abstract : Granulomatous hepatitis may present with abdominal pain. Four patients are described who had longstanding severe abdominal pain associated with this condition.